Free-breathing, non-contrast, three-dimensional whole-heart coronary magnetic resonance imaging for the identification of culprit and vulnerable atherosclerotic plaque - Hajhosseiny, Reza; Hartley, Adam; Cole, Graham; Munoz, Camilla; Sethi, Amarjit; Al-Lamee, Rasha; Khawaja, Saud; Zaman, Sameer; Howard, James; Gopalan, Deepa; Ariff, Ben; Kaprielian, Raffi; et al. (Journal of cardiovascular magnetic resonance, 2025)
Detection of vulnerable coronary plaque can predict future myocardial infarctions. We have developed a novel, non-contrast cardiovascular magnetic resonance sequence (iT2prep-BOOST), enabling simultaneous, co-registered coronary angiography and plaque detection. To validate iT2prep-BOOST in patients with non-ST-segment elevation myocardial infarction (NSTEMI). 41 patients with suspected NSTEMI were recruited. Invasive coronary angiography ± intravascular imaging was used to classify coronary segments into the following categories: normal, non-culprit and culprit segments; stenosed segments as well as segments with vulnerable plaque features (lipid, calcium, fibroatheroma, thin cap fibroatheroma (TCFA), plaque-rupture and thrombus). The plaque/myocardial signal intensity ratio (PMR) in each coronary segment was analyzed on iT2prep-BOOST. The mean ± standard deviation PMR of culprit segments was significantly higher than non-culprit segments and normal segments (1.01±0.14 vs. 0.67±0.18 vs. 0.35±0.24, P<0.001, respectively). Coronary segments with lipid, calcium, and fibroatheroma had a significantly higher PMR compared to normal coronary segments (P<0.001), but significantly lower than segments with plaque-rupture and intraluminal thrombus (P<0.05). There was a progressive increase in PMR with increasing coronary segment stenosis (P<0.001). There was a significant association on multivariable analysis between HbA1c as well as family history of coronary artery disease and mean PMR (P=0.05 and P=0.04, respectively). iT2prep-BOOST has the potential to simultaneously visualize coronary artery lumen and plaque and differentiate normal segments from non-culprit and culprit plaque segments non-invasively and without contrast. The prognostic value of PMR needs to be investigated in a prospective multicenter study. [Display omitted]